Feasibility study of the Oxy Fuel Gas Welding (OFW) process in AA2024-T3 and GF/PEI composite hybrid joint - Reis, Jonas Frank [UNESP]; Marques, L. F.B. [UNESP]; Abrahao, A. B.M.; Nakazato, R. Z. [UNESP]; Botelho, E. C. [UNESP] (Springer Nature, 2021)
The aim of the present study is evaluating the feasibility of Oxy Fuel Welding (OFW), using liquefied petroleum gas (LPG), for the joining of the glass fiber/polyetherimide composite and aluminum alloy 2024-T3, which combine the effectiveness of the joint and the low cost of operation. A statistical experimental design was performed to determine by OFW parameters, and the samples were welded and evaluated after Lap Shear Strength (LSS) loading as the planning response variable. For a better result of the joint strength, through the mechanical interlock between the laminate and the AA2024-T3, anodization process was performed. A maximum value of LSS with 6.20 MPa was obtained, with optimized values reaching 6.32 MPa. The results of mechanical resistance of the hybrid junction involving the anodized AA2024-T3 were doubled, being 13.80 MPa in relation to the maximum obtained from the joint without treatment, confirming the increase of the interaction between these two materials. This fact was confirmed by the roughness test and optical microscopy. After welding, the AA2024-T3 structure was converted into a new structure of equiaxed grains, from the recrystallization of the grains, the hardness value being reduced by approximately 24%. From the TGA and EDS analyses, there was no significant difference in the degradation temperature of the thermoplastic composite, confirming the efficacy of the process for hybrid joint AA2024-T3 and GF/PEI composite, and there is no indication of contaminant that could interfere with the quality of the weld.
Keywords: Aluminum alloy 2024-T3; Glass fiber/polyetherimide composite; Joining process; Oxy Fuel Welding (OFW)